PTEN-L is a novel protein phosphatase for ubiquitin dephosphorylation to inhibit PINK1-Parkin-mediated mitophagy - Wang, Liming (2020)
Mitophagy is an important type of selective autophagy for specific elimination of damaged mitochondria. PTEN-induced putative kinase protein 1 (PINK1)-catalyzed phosphorylation of ubiquitin (Ub) plays a critical role in the onset of PINK1-Parkin-mediated mitophagy. Phosphatase and tensin homolog (PTEN)-long (PTEN-L) is a newly identified isoform of PTEN, with addition of 173 amino acids to its N-terminus. Here we report that PTEN-L is a novel negative regulator of mitophagy via its protein phosphatase activity against phosphorylated ubiquitin. We found that PTEN-L localizes at the outer mitochondrial membrane (OMM) and overexpression of PTEN-L inhibits, whereas deletion of PTEN-L promotes, mitophagy induced by various mitochondria-damaging agents. Mechanistically, PTEN-L is capable of effectively preventing Parkin mitochondrial translocation, reducing Parkin phosphorylation, maintaining its closed inactive conformation, and inhibiting its E3 ligase activity. More importantly, PTEN-L reduces the level of phosphorylated ubiquitin (pSer65-Ub) in vivo, and in vitro phosphatase assay confirms that PTEN-L dephosphorylates pSer65-Ub via its protein phosphatase activity, independently of its lipid phosphatase function. Taken together, our findings demonstrate a novel function of PTEN-L as a protein phosphatase for ubiquitin, which counteracts PINK1-mediated ubiquitin phosphorylation leading to blockage of the feedforward mechanisms in mitophagy induction and eventual suppression of mitophagy. Thus, understanding this novel function of PTEN-L provides a key missing piece in the molecular puzzle controlling mitophagy, a critical process in many important human diseases including neurodegenerative disorders such as Parkinson's disease.